The Effect of Sinergic Transformational Leaders, Academic Culture On The Sustainability Organization Performance of University Lecturer in Indonesia of the Corona Virus (Covid-19) Era - Lisnatiawati Saragih; M Noor Salim; Syafrizal Chan; Mafizatun Nurhayati (Jurnal Doktor Manajemen (JDM), 2021)
The study aims to determine and analyze the effect of transformational leaders, academic culture on of the Sustainability Organization Performance  of University Lecturers in Indonesia of the Corona Virus (Covid-19) era. This study use quantitative research method with survey technique to respond the test hypotheses that have been formulated. The respondents are 150 lecturers, the sampling technique used was cluster random sampling technique. The instrument of transformational leader, academic lecture and Sustainability Organization Performance  were validated with the product moment correlation, while reliability was measured by the Alpha Cronbach. Hypothesis testing using path analysis. The results of data analysis using path analysis, showed that, (1) there is the effect of direct transformational leaders on the lecturers Sustainability Organization Performance , (2) there is the effect of direct academic culture on the lecturers Sustainability Organization Performance , and (3) there is the effect of direct sinergic transformational leaders on the lecturers academic culture. Implications of research efforts to bring down the lecturers Sustainability organization Performance , the effectiveness of sinergic transformational leaders must be increased, the improve the effectivity of academic culture.           Keyword:  Sinergic Transformational Leaders, Academic Culture On The Sustainability Organization Performance